Negative relationship between risk and return: A contrary view - Iqbal Mahmood; Syed Zulfiqar Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
According to standard finance, risk and return are positively correlated, but many studies conducted in the behavioral finance and prospect theory context have revealed that risk and return are not positively correlated, but are negatively correlated. In this study, effort has been made to examine the nature of relationship between these two variables. Data used in this study is of secondary nature and its span is from 1995-2011. Spearman rank order correlation has been used to test this relationship between risk and return. Results indicated that when correlation test has been applied on the whole data set, risk and return are found to be negatively correlated in below target return companies, while these two are positively correlated in above target return companies. These findings exhibit that implications of prospect theory with respect to risk-return relationship are found true when the whole data sample is tested as one unit. But, when the same sample is subdivided into five segments or sections, results change and show a mixed pattern. Implications of prospect theory with regard to risk return relationship in such a situation are partially proved in few sectors.
Keywords: 330; reference point; behavioral finance; risk averse; risk seeking; ex-post return